Effects of cutting weight via sauna on force production and rate of force development for the olympic snatch pull - Budd II, B. R.; Jensen, R. L. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
This study examined the effects of cutting weight on ground reaction force (GRF), rate of force development (RFD) for the snatch pull. Vertical jump (VJ) was also tested compared to normal conditions. Olympic male weightlifters (n=7) used sauna and food/water restrictions (SW) to achieve 1-2% body mass loss. Snatch pull peak vertical GRF, RFD and VJ height after SW didn`t differ from control pulls (p >0.05). Mean (±SD) GRF for control = 2405 ± 381 N; while after cutting weight and sauna = 2241 ± 404 N. VJ control after pulls mean = 56.0 ± 9.7 cm. Vertical jump on the weight cut day after pulls mean = 58.0 ± 9.2 cm. GRF decreased by 12.7% and VJ increased by 3.4% after weight cutting compared to control; however, these performance variables were not significantly different from the control condition (p > 0.05).